2015
DOI: 10.3233/jad-142229
|View full text |Cite
|
Sign up to set email alerts
|

Visual Versus Semi-Quantitative Analysis of 18F-FDG-PET in Amnestic MCI: An European Alzheimer's Disease Consortium (EADC) Project

Abstract: We aimed to investigate the accuracy of FDG-PET to detect the Alzheimer's disease (AD) brain glucose hypometabolic pattern in 142 patients with amnestic mild cognitive impairment (aMCI) and 109 healthy controls. aMCI patients were followed for at least two years or until conversion to dementia. Images were evaluated by means of visual read by either moderately-skilled or expert readers, and by means of a summary metric of AD-like hypometabolism (PALZ score). Seventy-seven patients converted to AD-dementia afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
60
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 51 publications
(67 reference statements)
11
60
1
Order By: Relevance
“…The discriminating power of visual or fully automated analysis of 18 F-FDG imaging improves in research scenarios, for example, to differentiate MCI subjects who converted to AD dementia from normal control subjects (18,19). However, this does not closely resemble clinical routine.…”
Section: Discussionmentioning
confidence: 99%
“…The discriminating power of visual or fully automated analysis of 18 F-FDG imaging improves in research scenarios, for example, to differentiate MCI subjects who converted to AD dementia from normal control subjects (18,19). However, this does not closely resemble clinical routine.…”
Section: Discussionmentioning
confidence: 99%
“…We used a summary metric of metabolism in order to test the impact of reserve on an objective and robust index. Previous studies have shown that visual analyses or visual interpretation of voxelwise outputs might be superior to summary metrics for diagnostic purposes [20]. However, the impact of different levels of education on the visual interpretation of statistical maps would be difficult to estimate given the lack of an objective cut-off.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that what is being reimbursed are image acquisition and the traditional visual subjective readout, 40 which is operator-dependent. 41 MRI scanning is reimbursed widely, but often the indication is the exclusion of alternative causes (non-degenerative or surgical) of cognitive impairment rather than the positive diagnosis of AD through assessment of, e.g., medial temporal atrophy. When surveyed in 2009, CSF biomarkers were reimbursed in only about half of European countries.…”
Section: 5mentioning
confidence: 99%